Self-Directed Learning Mahasiswa Keperawatan pada Implementasi E-Learning di Pembelajaran Praktik Profesi Ners - Kharisma Eka Suryani; Made Satya Nugraha Gautama; Eri Yanuar Budi Akhmad Sunaryo; Totok Harjanto (PSIK FKKMK UGM, 2022)
Background: E-learning method could develop student’s self-directed learning abilities, as its advantage. Self-directed learning (SDL) becomes essential in education since it encourages student to learning, skill development, and professional practice. Educators need to combine current learning process with information technology and e-learning to promote student readiness for SDL abilities.Objective: To describe self-directed learning readiness (SDLR) for nursing students during e-learning implementation in clinical rotation nurse professional program.Method: This was a descriptive-quantitative study with a cross-sectional design conducted at PSIK FK-KMK UGM. Total sampling was applied and included 102 respondents. They were nurse professional program students who were taking basic nursing practice and nursing management courses from August to December 2018. Self-Directed Learning Readiness Scale (SDLRS) was used as data collection instrument which consisted of 40 items. Data was analysed using univariate approach.Result: There were 60,8% of Nurse Professional Program students who took e-learning courses had high SDLR scores (Mean=152,75; SD=13,362; Min=121; Max=195). The average SDLR scores in each subscale were reaching 3,61 on self-management, 3,98 on the desire to learn, and 3,86 on self-control.Conclusion: The SDLR level of nurse professional program students who took basic nursing practice and nursing management courses showed high results in the implementation of e-learning. ABSTRAKLatar belakang: E-learning memiliki keunggulan dalam mengembangkan kemampuan belajar mandiri siswa (self-directed learning). Self-directed learning (SDL) penting dalam pendidikan karena memotivasi mahasiswa untuk belajar, mengembangkan keahlian, serta melatih profesionalitas. Pendidik perlu menggabungkan proses pembelajaran dengan teknologi informasi dan e-learning guna memfasilitasi kesiapan mahasiswa terhadap kemampuan SDL (self-directed learning readiness).Tujuan: Untuk mengetahui gambaran SDLR mahasiswa profesi ners.Metode: Penelitian ini merupakan penelitian descriptive-quantitative dengan rancangan cross sectional yang dilakukan di PSIK FK-KMK UGM. Pengambilan responden secara total sampling, responden sebanyak 102 mahasiswa profesi ners stase praktik keperawatan dasar dan manajemen keperawatan pada periode Agustus-Desember 2018. Instrumen yang digunakan adalah Self-Directed Learning Readiness Scale (SDLRS) yang terdiri atas 40 pertanyaan. Data penelitian dianalisis menggunakan analisis univariat.Hasil: Sebanyak 60,8% mahasiswa profesi ners pada pembelajaran e-learning ini memiliki nilai SDLR yang cenderung tinggi (Mean=152,75; SD=13,362; Min=121; Max=195). Rata-rata skala SDLR pada tiap sub-skala adalah 3,61 pada manajemen diri, 3,98 pada keinginan untuk belajar, dan 3,86 untuk kontrol diri.Simpulan: Tingkat SDL mahasiswa profesi ners menunjukkan kecenderungan tinggi pada pembelajaran e-learning.